Efek Media Massa terhadap Agama dan Sosial Budaya Masyarakat - Benny Munardi (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2021)
The effect of mass media has a very important role in the formation of one's moral and personality characteristics. The purpose of writing this journal is to explain and describe in detail how the strong influence of the mass media, both positive and negative influences that occur on individuals in society, especially in religion and social society. The method used in this paper uses a descriptive analysis method of the changes that occur in Indonesian society in particular and the world community globally. The description uses samples that occur from the opposite life of the local cultural life of a community of countries with the effect of being contaminated with foreign countries that are powerful in dominating the vision and mission of the mass media launched. The results obtained that the mass media can have a positive effect and can also hurt society. The media cannot dictate society. But it is the people who choose which media they want to see. Religion can be a filter in receiving mass media messages to us